Assessing the Assessor: Investigating Formative Assessment Literacy Among Islamic Education Teachers in Lamongan, Indonesia - Zuhriyyah Hidayati; Nurdi Nurdi; Kusaeri Kusaeri; Suparto Suparto; Sita Isna Malyuna (STAI Hubbulwathan Duri, 2025)
Formative assessment literacy is essential for effective and student-centered instruction, yet limited research explores its application within religious education. This study investigates the level of formative assessment literacy among Islamic Education (PAI) teachers in Lamongan, East Java, focusing on three dimensions: conceptual understanding, practical implementation, and socio-emotional awareness. A descriptive quantitative design was employed, involving 263 PAI teachers from elementary to secondary levels. Data were collected using a validated Likert-scale questionnaire adapted from the Teacher Formative Assessment Literacy Scale (TFALS). Descriptive statistics and linear regression analysis were used to examine literacy levels and the predictive contribution of each dimension. The results show that PAI teachers exhibit high levels of formative assessment literacy across all three dimensions, with mean scores exceeding 5 on a 6-point scale. Regression analysis confirmed that each dimension significantly and independently contributes to teachers’ perceptions of formative assessment. However, interaction effects between dimensions were not significant, indicating limited cross-dimensional integration. These findings suggest that while PAI teachers possess strong individual competencies in assessment, holistic integration remains a challenge. Professional development should therefore address not only technical knowledge but also foster reflective and emotional capacities. Strengthening these areas can support more inclusive, ethical, and responsive assessment practices, particularly in value-based educational contexts such as Islamic education.